The impact of task level demands, work group level support and affective commitment on emotional exhaustion among services managers: A mediating moderating perspective. Issue 4 (13th November 2017) - Laila, Ume; Hanif, Rubina
Abstract : Purpose: This study aims to explain the effects of affective commitment as a mediator between task-level job demands (quantitative workload, qualitative workload, feedback and role conflict) and emotional exhaustion among service mangers. Design/methodology/approach: Sub-scales of task-level demand and work group-level resources have been selected from job demands and resources indigenous scale. While emotional exhaustion was measured with the subscale of Maslach burnout inventory. For this purpose, data were obtained from 239 respondents to check the relationship between variables. Amos 21 was used to analyze the model fit among variables. Findings: The results of the study show that there is a significant positive relationship between high task-level demands and emotional exhaustion. The results also signify that affective commitment partially mediates the relationship. Research limitations/implications: The present study is cross-sectional in design, whereas longitudinal studies would be effective to explain causality relationship. Term of service managers is also not well defined. Data were collected as per the convenient sampling technique. Originality/value: The research is based on PhD thesis by the author.